Intermittent docetaxel chemotherapy as first-line treatment for metastatic castration-resistant prostate cancer patients. (March 2015) - Caffo, Orazio; Lo Re, Giovanni; Sava, Teodoro; Buti, Sebastiano; Sacco, Cosimo; Basso, Umberto; Zustovich, Fable; Lodde, Michele; Perin, Alessandra; Facchini, Gaetano; Veccia, Antonello; Maines, Francesca; et al.
ABSTRACT : Aims: The intermittent administration of chemotherapy is a means of preserving patients' quality of life (QL). The aim of this study was to verify whether the intermittent administration of docetaxel (DOC) improves the patients' QL.Patients & methods: All patients received DOC 70 mg/m 2 every 3 weeks for eight cycles. The patients were randomized to receive DOC continuously or with a fixed 3-month interval after the first four DOC courses.Results: The study involved 148 patients. There was no difference in QL between the groups receiving intermittent or continuous treatment. Intermittence had no detrimental effects on disease control.Conclusion: Although feasible and not detrimental, our results showed that true intermittent chemotherapy in metastatic castration-resistant prostate cancer patients failed to improve the patients' QL.